Peningkatan Hasil Belajar Melalui Model Pembelajaran Numbered Head Together Berbantuan Media Game Teka Teki Silang Siswa Kelas IV Sekolah Dasar - Saiful Anam; Sekar Dwi Ardianti; Much Arsyad Fardani (PGSD Universitas Muria Kudus, 2023)
The purpose of this study is to analyze the application of the Numbered Head Together learning model assisted by Crossword Game media in improving student learning outcomes.The research method used is classroom action research (CAR). The research was carried out from March 21 2022 to March 28 2022 in class IV SD 1 Gulang Mejobo Kudus. Data collection techniques used are tests, documentation, and observation. Data validation uses the opinion of experts (Experts Judgment) by Ms. Sekar Dwi Ardianti, S.Pd., M.Pd., and Mr. Much. Arsyad Fardani, S.Pd., M.Pd. Data analysis in this study used quantitative and qualitative data.The results showed that the learning outcomes of students' knowledge domain increased significantly between the first cycle of 70.29% and the second cycle of 74.70%. This proves that the application of the Numbered Head Together learning model assisted by the Crossword Puzzle Game media can improve the learning outcomes of fourth grade students at SD 1 Gulang.